Immunohistochemical localization of renin-containing cells in two elasmobranch species - Lacy, E. R.; Reale, E.; Luciano, L. (Fish physiology and biochemistry, 2016)
Renin immunoreactivity was localized at the light and electron microscopic level in two elasmobranch fish species, the Atlantic stingray, Dasyatis sabina , and river ray, Potamotrygon humerosa . At the light microscopic level, the peroxidase–anti-peroxidase method showed a positive immunoreactivity in modified smooth muscle cells in kidney afferent arterioles as well as in arterioles of several organs: rectal gland, inter-renal gland, conus arteriosus, and gill. Electron microscopic renin-positive immunogold localization was confined to the contents of membrane bound granules in the modified smooth muscle cells of these arterioles. The presence of renin-containing granules in the modified smooth muscle, “granular cells,” of the renal glomerular afferent arteriole of these two stingray species adds support to earlier studies which showed the structural components of a complete juxtaglomerular apparatus and some of the biochemical and molecular components of a renin–angiotensin system (RAS) as found in teleost fish, reptiles, birds, and mammals. A notable result, however, was the renin-positive immunoreaction in the arteriolar wall of all other organs studied here. The presence of this “diffuse renin system” in the connective tissue of various organs suggests that in these two stingray species in addition to local organ-specific functions, the RAS may act as a systemic mechanism to regulate blood pressure and blood flow in the body.